THE TRANSFORMATION PERIODS IN THE RUSSIAN-TURKISH RELATIONS (1991-2016) - D. G. Bdoyan (Vestnik MGIMO-Universiteta, 2017)
Russian-Turkish relations, spanning more than five centuries, have gone through a number of trials. However, at the end of the 20th and at the beginning of the 21st century these relations became especially dynamic. Transformations of the relations occur now more often and exert serious impact both on the states, and on the region in general. The collapse of the USSR can be considered as the beginning of intensive changes in the relationship between Russia and Turkey. The geopolitical competition in the post-soviet area, economic cooperation and the threat of terrorism were the main points of interaction. Gradual transition of Russian-Turkish relations from competition to multidimensional partnership began in the early 2000s, with the election of president V. V. Putin in Russia and with the coming to power in Turkey of the Justice and Development Party. The new form of partnership was promoted as being vital for cooperation in Eurasia for resolution of conflicts, combatting terrorism, trade and energy sphere. Further development of the relations resulted in willingness of the two countries to transition from a multidimensional to a strategic partnership. The beginning of this process started in 2009. Nevertheless, shortly thereafter disagreements concerning the events in the Middle East, with the beginning of the «Arab Spring» began to have a negative impact on the bilateral relations. The situation surrounding Ukraine also had its negative effect. Even so, the economic relations and cooperation in the energy and trade spheres continued to develop, up to the tragic events related to the shoot-down of the Russian bomber aircraft SU-24 in November 2015. After this, the Russian-Turkish relations deteriorated to their lowest point, practically in all spheres. Since August 2016 the relations have been gradually improving. This led to the restoration of political dialogue, improvement of the economic relations and to the realization of the energy projects frozen earlier. The article studies historical and contemporary stages of the transformation of RussianTurkish relations to understand the causes of these changes and their impact on the further dynamics of bilateral relations. The main research methods are the historical method for disclosing the retrospective and contemporary development of Russian-Turkish relations and the comparative method for comparing the nature and scale of bilateral interaction at various historical stages. As a result of the research it was found out, that historically, there is no progressive and stable development in the Russian-Turkish relations. At the same time, the causes of negative transformations are directly related to geopolitical competition for influence in regions, and positive changes are mainly due to economic interests, especially in the energy sector. At the same time, there is no division of economic and political interests, often serious disagreements on regional issues lead to the severance of economic ties and vice versa, economic cooperation has a positive impact on bilateral relations.